THE PROBLEM OF SELECTING STANDARDS. - Moyer, C. A. (The Accounting Review, 1948)
Abstract During the past year a committee was appointed by the American Accounting Association to consider the rating of curriculum and instructional standards among the various institutions of higher learning having accounting courses. It might seem reasonable to require that the accounting work should be offered in a school or college of business and not in some other division of the college or university, in order to secure proper integration of accounting with important related subject matter. It is taken for granted that graduate work requires the extensive use of current periodicals, reference books, and other library facilities, and therefore graduate students in accounting should have access to them. The adequacy of library facilities might be measured quantitatively by the number of bound volumes on hand, or by the amount expected annually for library purposes.